Open Secrets - Dhar, Maloy Krishna (New Delhi, 2005)
The narratives in this work have candidly unveiled certain well guarded vaults with the intention of appealing to the discerning readers, scholars, to bring pressure for devising constitutional laws.
Keywords: Intelligence